Design and development of augmented reality advertisement visual production through multi-method approach / Fatrisha Mohamed Yussof ... [et al.] - Mohamed Yussof, Fatrisha; Idris, Nurkhazilah; Mohamed Salleh, Sabariah; Ahmad, Abdul Latiff (Faculty of Art and Design, 2023)
The emergence of immersive new media in advertising, such as augmented reality (AR), has accelerated since the Industrial Revolution 4.0. Companies use different tools to shape a brand by providing a higher level of interaction in AR for their new marketing. However, influencing consumer decisions despite consumers' lack of attention is also a critical task in measuring the effectiveness of advertising. Thus, this research aims to design and develop different approaches to advertisement prototypes as stimuli for experiments to measure AR ads' effectiveness on consumers. This research design consisted of a multi-method to produce three ideations of AR advertisement prototypes. The respondent selection is based on convenient sampling, and n=44 respondents participated. Firstly, the researcher conducted a visual analysis to extract the elements used in the ads based on ethos, pathos, and logos by Aristotle's concept. Secondly, the study adopted inter-rater reliability measurement to analyze the degree to which the judgments of the several judges were consistent. Lastly, a descriptive AR advertisement's design and development of the AR ads process framework are described. The results show that respondents' degree of agreement leads to a mutual understanding of the subject and appeals categorized as creative ads, endorsement ads, and argument quality ads. The process also helps to speed up the application development. The apps use marker-based AR to display 3D models or video commercials and provide information on product design that gives users control of the interface. Finally, a plan for future research in AR advertising is specified, beta testing for the usability of the apps is recommended for future research, and the implications are discussed.